2021
DOI: 10.1016/j.psj.2020.11.063
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of intestinal genes in necrotic enteritis challenged broiler chickens with 2 different Clostridium perfringens strains

Abstract: The primary cause of necrotic enteritis ( NE ) disease in chickens is the NetB-positive Clostridium perfringens bacterium. Many factors are known to affect the severity of NE in the challenge models of broiler chickens, and one of these factors is the virulence of C. perfringens strain. This study was conducted to evaluate the effect of 2 pathogenic C. perfringens strains in a NE challenge model on gut health and mRNA e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 83 publications
3
10
0
Order By: Relevance
“…The results observed in the current study showed that NE challenge downregulated OCLN in male birds and MUC2 in both male and female birds. These results were consistent with previous findings in broilers where birds challenged with NE had downregulated OCLN genes [ 41 ]. Interestingly, CLDN1 and JAM2 were upregulated by NE challenge, and it is contrary to their function as tight junction proteins.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results observed in the current study showed that NE challenge downregulated OCLN in male birds and MUC2 in both male and female birds. These results were consistent with previous findings in broilers where birds challenged with NE had downregulated OCLN genes [ 41 ]. Interestingly, CLDN1 and JAM2 were upregulated by NE challenge, and it is contrary to their function as tight junction proteins.…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, CLDN1 and JAM2 were upregulated by NE challenge, and it is contrary to their function as tight junction proteins. However, as discussed by Gharib-Naseri et al [ 41 ], the upregulation of CLDN1 may not be an indication of better tight junction function but other mechanisms may be involved. Therefore, we speculate that it may not be a good marker for the indication of gut integrity at least in the NE challenge studies.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al [59] confirmed the significant effect of NE on immunoglobulin genes evidenced by the reduced expression of IgA+ B cells in birds infected with NE. Similarly, Gharib-Naseri et al [35] reported a reduced expression of IgG and IgM genes in NE challenged birds. In the current study, upregulation of IgG gene in birds fed MG and MGFA compared to the NC group indicates that the birds fed additives had a greater immune response.…”
Section: Discussionmentioning
confidence: 85%
“…The expression of TJP1 gene is correlated with other tight junction genes in the epithelium [52]. Enteric diseases such as NE damage intestinal integrity and downregulates tight junction gene expression (CLDN, OCLN, and TJP1), resulting in increased intestinal permeability [35,53,54]. However, it should be noted that damage in the intestinal epithelium and disturbances in the function of genes regulating tight junctions and immunity can be due to the Eimeria-caused infections prior to C. perfringens challenge of the birds.…”
Section: Discussionmentioning
confidence: 99%
“…All these indicate that broiler chickens can be used to study the effect of disturbances in the gastrointestinal microflora, which in turn significantly affect the absorption of nutrients [ 20 ]. Numerous recent studies showed changes in gene expression of proteins are responsible for intestinal tight junction integrity or barrier function (claudin-1, occludin, mucin-2, Fatty acid-binding protein-2) in broiler chickens during gut inflammation induced by C. perfringens challenge, which are similar to those observed in humans during the IBD [ 47 , 48 , 49 , 50 ]. Broiler chickens are also sensitive to C. perfringens , which facilitated the infection process itself.…”
Section: Discussionmentioning
confidence: 89%